Dramatically changed immune‐related molecules as early diagnostic biomarkers of non‐small cell lung cancer. (20th September 2019) - Ye, Xiangdong; Zhang, Ni; Jin, Yanxia; Xu, Bo; Guo, Chanyuan; Wang, Xueqing; Su, Yanting; Yang, Qing; Song, Jiaqi; Yu, Wenhui; Cheng, Pengfei; Cheng, Liming; et al.
Abstract : Non‐small cell lung cancer (NSCLC) is the main type of lung cancer, with a low 5‐year survival rate because of the absence of effective clinical biomarkers for early diagnosis. Based on the immunosurveillance theory, we proposed that changes in the immune system are more pronounced than tumour‐associated antigens during the early stage of cancer. Therefore, a new strategy was designed to screen early diagnostic biomarkers from peripheral leukocytes in early‐stage NSCLCs with transcriptome sequencing. A total of 358 immune‐related differentially expressed genes were identified between early‐NSCLC patients and healthy individuals. Orosomucoid‐1 (ORM1, a acute phase protein), the total ORM and chitotriosidase‐1 (involved in degradation of chitobiose) were selected for further verification in 210 serum samples by western blotting, ELISA and nephelometry immunoassay (based on immuno‐scatter turbidmetry). Receiver operating characteristic curve analysis show that ORM1 and total ORM have excellent diagnostic efficacies, with area under the curve of 0.862 and 0.920, respectively, which significantly distinguished very early‐NSCLC (IA) from healthy samples. Flow cytometry results showed that CD15 + neutrophils made up 73% of ORM1 + peripheral leukocytes. In mouse lung cancer model, serum ORM1, but not liver ORM1, changed significantly in the early stage of NSCLC. ORM1 expression in peripheral leukocytes was regulated by TGF‐β and mediated by the TGF‐β/Smad signalling pathway. Our results indicated that combined ORM and TGF‐β could be a promising clinical biomarker in the diagnosis of early NSCLC. Abstract : Based on the immunosurveillance theory, the expression of immune‐related genes in peripheral leukocytes of early‐non‐small cell lung cancer (NSCLC) patients and healthy individuals was investigated in this paper. Orosomucoid (ORM) in serum, which significantly decreased in early‐NSCLCs, showed high diagnostic efficacies (AUC = 0.920). The expression of ORM1 in peripheral leukocytes was regulated by TGF‐β/Smad signalling pathway. Combination of ORM and TGF‐β (AUC = 0.985) could be a promising clinical biomarker in the diagnosis of early NSCLC.